Modern Means and Methods of National-Patriotic Education of Future Border Guard Officers in Foreign Language Classes - Nadiia Moroz (Pedagogical Discourse, 2018)
The purpose of the article is to analyze the modern means and methods of national-patriotic education of future border guard officers in foreign language classes. On the basis of the conducted analysis it is determined that teaching and upbringing of cadets in foreign language classes must be considered as a simultaneous process under the teacher’s supervision. The tasks of national-patriotic education of the cadets along with the formation of their foreign language communicative competence have been defined. The attention is focused on the border guards’ patriotism education. The patriotism of the border guards manifests itself in love for the Motherland and perfect possession of the state language, helping to establish Ukraine as a sovereign, legal, democratic, social state, readiness to defend its independence, serve and protect it, respect the state symbols of Ukraine, the symbols of the State Border Guard Service of Ukraine, Ukrainian customs. It is noted that the effectiveness of patriotic education depends, to a large extent, on the orientation of the educational process, the forms, means and methods of its organization. Educational influence in foreign language classes is provided through the use of educational material and special methods of working with it, thus forming the corresponding socio-political views of the cadets, their feelings, attitude to the moral and ethical categories. It is discovered that among the methods and forms of patriotic education, the main role belongs to the active methods of learning based on the democratic style of interaction, which contribute to the formation of critical thinking, initiative and creativity. Methodical recommendations for teachers in order to educate the cadets’ patriotism during foreign language classes have been developed. On the basis of generalization it is stated that the modern means and methods the teacher chooses and how fully he can reveal the educational potential of the educational material depend on the teacher's professionalism, his patriotic sentiment and dedication to his work. A teacher of a foreign language should grab cadets with his subject and the country whose language is studied, but he must still remain a patriot of his own country.